Studying grain color diversity in the barley collection of VIR - A. Y. Glagoleva; L. A. Novokreschenov; O. Y. Shoeva; O. N. Kovaleva; E. K. Khlestkina (Труды по прикладной ботанике, генетике и селекции)
Background. Dark color of barley grain (Hordeum vulgare L.) can be caused by the synthesis and accumulation of two types of polyphenolic pigments – anthocyanins and melanins, which perform important functions in plant life, participating in the regulation of growth and development, and protecting plants from adverse environmental conditions. The aim of this study was to investigate the diversity of barley in the VIR collection in the context of grain color.Materials and methods. To analyze the pigment composition of the grain, 150 barley accessions with colored grains were selected from the VIR collection. Anthocyanins and melanins in grain husk were identified using qualitative reactions.Results and discussion. It was shown that in 60% of the accessions the dark color of their grain was induced by independent accumulation of melanin, while the accessions characterized by accumulation of only anthocyanins, and those with combined accumulation of anthocyanins and melanins, were 14.6% and 14%, respectively. For 11.3% of the accessions the presence of anthocyanins and melanins in grain husk was not found; their pigmentation could presumably be associated with an increased content of other polyphenolic pigments – proanthocyanidins. Accessions with melanin in grain predominated in all identified geographic groups, while other types of pigmentation were most evenly represented in the regions with the widest genetic diversity of barleys – Africa, East Asia, and the Middle East.Conclusion. Dark pigmentation of barley grain was shown to be mainly associated with the accumulation of melanin, and this type of pigmentation prevails in all geographical regions identified. The results obtained made it possible to describe the barley collection more fully and expand the possibilities of its utilization.